Accounting in 2036: A Learned Profession - Barth, Mary E. (The Accounting Review, 2018)
ABSTRACT My vision is that by 2036 accounting is known as the learned profession that provides information for informed decision-making to support a prosperous society. By 2036, academic and practicing accountants view themselves as part of the same profession, and practicing accountants look to academics to develop knowledge relevant to identifying information—and its characteristics—useful in informing decisions. In sum, insights from research are instrumental in shaping accounting in practice. To achieve this vision, academics need to (1) conduct fundamental and applied research; (2) communicate research insights outside of academia; (3) interact with practicing accountants and others who use accounting information, such as managers, capital providers, regulators, and government officials; and (4) ensure that everyone understands that academic accountants are responsible for the “learned” part of accounting as a learned profession.